2016
DOI: 10.1097/md.0000000000004827
|View full text |Cite
|
Sign up to set email alerts
|

Undiagnosed connective tissue diseases

Abstract: Among different subgroups of pulmonary arterial hypertension (PAH), those associated with connective tissue diseases (CTDs) have distinct hemodynamic and prognostic features; a correct etiologic diagnosis is thus mandatory.To estimate frequency and prognosis of previously undiagnosed CTDs in a suspect idiopathic (i) PAH cohort.Consecutive patients with PAH confirmed by right heart catheterization referred at the Cardiology Division of our Hospital without a previous rheumatological assessment or the occurrence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…SSc patients are mainly treated by anti-inflammation, immunoregulation, treatment of vascular lesion and anti-fibrosis, which has a long treatment course and causes obvious adverse drug reactions ( 15 - 17 ). With various strong effects such as self-duplication, immunoregulation, vascularization promotion and secretion, MSC becomes the hot spot of treatment for autoimmune disease.…”
Section: Discussionmentioning
confidence: 99%
“…SSc patients are mainly treated by anti-inflammation, immunoregulation, treatment of vascular lesion and anti-fibrosis, which has a long treatment course and causes obvious adverse drug reactions ( 15 - 17 ). With various strong effects such as self-duplication, immunoregulation, vascularization promotion and secretion, MSC becomes the hot spot of treatment for autoimmune disease.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, 1 of the 40 patients (2.5%) was initially diagnosed as SS-associated PAH. This result is consistent with a similar study reported by Cavagna et al ., showing that only 1 out of 49 suspected idiopathic PAH patients (2.0%), have met the criteria of SS syndrome at the time of the initial evaluation [ 28 ]. We have additionally found that 5 out of the 25 patients who were initially diagnosed with idiopathic PAH was later diagnosed as primary SS.…”
Section: Discussionmentioning
confidence: 99%